Evaluation of kidney function in children with Hashimoto’s Thyroiditis (Annals of Medical Research, 2021)
Aim: Thyroid hormones have various effects on kidney function and both hypothyroidism and hyperthyroidism may result in clinically important alterations in kidney function. Therefore, we evaluated kidney functions and changes in kidney functions over time in children with Hashimoto thyroiditis (HT) who treated or not treated with thyroid hormone replacement therapy.Materials and Methods: The patients were divided into three groups. Group 1 included patients who had hypotroidism and received treatment, group 2 included patients who had euthyroid goiter and received treatment and group 3 consisted of patients who were clinically euthyroid and not received any treatment. All participants were followed prospectively. Serum creatinine (Cr), albumin and serum cystatin C (CysC) levels, estimated glomerular filtration rate eGFR, and urine protein to creatinine ratio (PCR) were measured at the time of diagnosis and one and six months after diagnosisResults: There were significant differences between baseline and follow-up characteristics of the group 1 in terms of serum Cr, urine PCR, CysC and eGFR. The baseline and follow-up characteristics of groups 2 and 3 were not statistically significant.Conclusion: Children with HT may present with kidney dysfunction and proteinuria, which improve with thyroid hormone replacement. We think that clinicians who follow children with HT should pay attention to this issue.